Prevalence and distribution of Taenia solium cysticercosis in naturally infected pigs in Punjab, India - Singh, Satinder Pal; Singh, Balbir Bagicha; Kalambhe, Deepali G.; Pathak, Devendra; Aulakh, Rabinder Singh; Dhand, Navneet K. (PLOS Neglected Tropical Diseases, 2018)
Background Taenia solium (T. solium) cysticercosis remains a neglected zoonotic disease in India. The current study was planned to estimate the prevalence of T. solium porcine cysticercosis in the Punjab state of India, to compare this prevalence with the disease prevalence in pigs reared outside Punjab and to assess the distribution of the parasite in pig carcasses. Methods Two slaughter shops were selected in each of the 22 districts of Punjab. Pigs slaughtered on the day/s of inspection were post-mortem inspected to identify the presence of T. solium cysts. Estimated true prevalence was estimated by taking into account the diagnostic sensitivity (38%) and specificity (100%) of post-mortem inspection using the Rogan-Gladen estimator. Positive carcasses were purchased and brought to the laboratory to assess the tissue distribution of T. solium cysts and to conduct PCR targeting large subunit rRNA gene, internal transcribed spacer 1 gene, ITS1 gene and Cytochrome oxidase I gene. The selected PCR products were submitted for sequencing and phylogenetic analyses were performed. Findings We contacted 71 shop owners to achieve a sample of 44 shops for the study. We inspected 642 pigs reared in Punjab and 450 imported from other states at these slaughter shops. In addition, we sampled 40 pigs from an abattoir located in the state capital. Of the 642 pigs reared in Punjab, 9 had T. solium cysts with an apparent prevalence of 1·40% (95% CI: 0·74%, 2·64%) and the estimated true prevalence of 3.69% (95% CI: 1·95%, 6·95%). Pigs imported from outside the state had a significantly higher prevalence (odds ratio: 2·58; 95% CI: 1·12, 5·98; p-value: 0·026) as 15 of the 450 imported pigs were positive (apparent prevalence: 3.33%; 95% CI: 2.03%, 5.43%; estimated true prevalence: 8.77%; 95% CI: 5.34%, 14.28%). None of samples was positive from the pigs sampled at the abattoir in the state capital. The PCR confirmed T. solium cysts from all the 24 positive samples. We counted a median of 897 (range 526–1964) cysts per infected pig from the 19 infected pig carcasses inspected. The phylogenetic tree based on the alignment of partial cytochrome oxidase 1 sequences indicated all positive samples to be clustered with the T. solium Asian genotype. The analysis did not indicate the presence of T. asiatica in the slaughter pigs. Conclusions Despite the underestimation of the prevalence due to missing mildly-infected carcasses, low participation and lack of representative sampling, the presence of heavily infected carcasses containing viable cysts, particularly those imported from outside the state, indicates that T. solium cysticercosis is an important food safety concern for pork consumers in Punjab, India. Measures should be taken to reduce the disease prevalence in pigs to reduce the disease burden in the public.